A review and framework of laser-based collaboration support. (2015) - Bechar, A.; Nof, S.Y.; Wachs, J.P.
Abstract: New technologies are emerging to enable and support physical, implicit and explicit collaborations. They are essential for dealing with increasingly complex systems in unstructured, dynamic environments. The purpose of this article is to review the role of laser technology in enabling better, more precise interactions and their control, and to identify opportunities and challenges in this area. While the most common applications of laser technology are found in medical and health care, manufacturing, and communication, other domains such as safety, quality assurance, agriculture, construction, entertainment, defense, transportation, and law enforcement also benefit from it. In spite of the rapid dissemination of this technology, its role in support of collaboration and discovery is still in its infancy. Research activities concerning new ways of using lasers as a collaboration supporting technology that may strengthen new areas have been relatively limited. Nevertheless, the translation to this domain of collaboration support has been recognized as vital for activities that demand increasingly more coordinated effort among interacting agents (e.g., humans, machines, particles) and digital, possibly also photonic agents. Recent advances in laser technology in a number of application domains are reviewed in this article, focusing primarily on lasers' role for supporting different forms of precision interactions and collaboration. In addition, a framework with five collaboration support functions and five collaboration dimensions is defined for this review. The taxonomy framework is useful for enabling better understanding of the existing and emerging opportunities that laser-based technology offers for collaboration support, its advantages and several research gaps.